Efficient and sustainable: innovative pot design for a Mediterranean small-scale fishery - Virgili, Massimo; Petetta, Andrea; Herrmann, Bent; Cerbule, Kristine; Guicciardi, Stefano; Li Veli, Daniel; Barone, Giulio; Lucchetti, Alessandro (Frontiers in Marine Science, 2024)
Pots are traditional fishing gear type largely employed in Mediterranean Small Scale Fisheries (SSFs). Their often higher species selectivity and catch quality compared to other gear types such as passive set nets or trawls are appealing characteristics for reducing the impact on benthic communities and diversifying fishing effort in the region. Despite this, in some SSFs, pots are still rarely used as prevalent gear due to low landings and profits. The present study investigated if an experimental pot design of two different colours could improve the catch efficiency for mantis shrimp (Squilla mantis) in the Adriatic coastal SSF, compared to the traditionally used design. The experimental design in white colour increased the catch efficiency for S. mantis compared to the same design in black colour and the traditional pots, while the catch efficiency for black goby (Gobius niger, another commercial species) was higher in the experimental design regardless of the colour.Furthermore, the species composition in catches was not significantly affected with the use of the experimental design, neither in target nor in bycatch species, therefore not causing negative effect on the species community.Finally, the experimental pot design also led to some improvements in gear durability, ensuring a higher resistance to wear, sea currents and marine fouling. The promising results obtained with this new design could broaden the interest towards increased use of pots as alternative and low impact gear in other Mediterranean areas.